Spectral Doppler, tissue Doppler, and speckle-tracking echocardiography for the evaluation of fetal cardiac function: an update - Peixoto,Alberto Borges (2021)
Abstract The functional assessment of the fetal heart has been incorporated into cardiac ultrasound screening as a routine procedure, encompassing fetuses with and without structural heart diseases. It has long been known that various cardiac and extracardiac conditions, such as fetal growth restriction, fetal tumors, twin-to-twin transfusion syndrome, fetal anemia, diaphragmatic hernia, arteriovenous fistula with high cardiac output, and congenital heart diseases (valvular regurgitation and primary myocardial disease), can alter hemodynamic status and fetal cardiac function. Several ultrasound and Doppler echocardiographic parameters of fetal cardiovascular disease have been shown to correlate with perinatal mortality. However, it is still difficult to identify the signs of fetal heart failure and to determine their relationship with prognosis. The aim of this study was to review the main two-dimensional Doppler ultrasound parameters that can be used in the evaluation of fetal cardiac function, with a focus on how to perform that evaluation and on its clinical applicability.